Key informant perspectives on overcoming HPV vaccination barriers in low-immunization NY counties - Samantha E. Hanley; Karina Ohri; Telisa Stewart; Maribel Vargas; Arielle Hanley; Elena C. Shaw; Nicholas Allis; Michael Seserman; Jana Shaw (Human Vaccines & Immunotherapeutics)
Human papillomavirus (HPV) infection is an important public health concern, with nearly 2,900 cases of HPV-related cancers reported in New York State (NYS) each year. Despite concerted efforts to enhance vaccine uptake in NYS, HPV vaccination rates among 13–15-year-olds failed to meet the 2020 healthy People target, and continue to lag behind the 2030 goal, of 80%. In counties with low immunization levels, understanding factors influencing decision-making among unvaccinated adolescents is crucial. This study aimed to identify barriers, facilitators, and potential interventions to improve HPV vaccine uptake. Qualitative semi-structured interviews were conducted with key informants in 15 NYS counties within the lowest quartile of HPV vaccine coverage among 13-year-old adolescents. Public health representatives, including Immunization Quality Improvement for Providers (IQIP) consultants, vaccine coordinators, medical directors, and primary care providers, were identified through purposive and snowball sampling. Interviews explored vaccination coverage knowledge, barriers and facilitating factors, and recommended strategies for improvement. All conversations were audio-recorded, transcribed, and analyzed using ATLAS.ti. Forty-four interviews were conducted, revealing barriers to HPV vaccination such as limited vaccine knowledge, vaccine misinformation, and accessibility. Key informants asserted barriers could be primarily addressed through education efforts, such increased public awareness, improved parent–doctor conversations, additional provider education on vaccine benefits, and supplementary education in patient spaces. Targeted education efforts and improved provider communication strategies have the potential to bolster HPV vaccination rates in NYS. These findings offer valuable insights for guiding future initiatives in communities facing significant barriers to vaccination.